Effect of B4C addition on the solidus and liquidus temperatures, density and surface tension of type 316 austenitic stainless steel in the liquid state - Fukuyama, Hiroyuki; Higashi, Hideo; Yamano, Hidemasa (Journal of nuclear materials, 2021)
•Solidus and liquidus temperatures of type 316 austenitic stainless steel − B4C system.•Density of molten type 316 austenitic stainless steel − B4C system.•Surface tension of molten type 316 austenitic stainless steel − B4C system.•Non-contact high-temperature thermophysical-property measurement technique. The effects of B4C addition on the solidus and liquidus temperatures of type 316 austenitic stainless steel (SS), and on the density and surface tension of molten SS, were experimentally studied. The solidus temperature of SS−x mass% B4C (0 ≤ x ≤ 10) monotonically decreased from 1666 to 1307 K with B4C addition. The liquidus temperature had a minimum at around 2.5 mass% B4C, and increased with further B4C addition up to 10 mass%. The density and surface tension of molten SS−x mass%B4C were successfully measured over a wide temperature range (including an undercooling region) via an electromagnetic-levitation technique. The density of each sample decreased linearly with temperature. The density also monotonically decreased with B4C content. Although the addition of B4C had no clear effect on the surface tension of SS−x mass%B4C, sulfur dissolved in SS316L caused a significant decrease in the surface tension.